2018
DOI: 10.24036/invotek.v18i2.257
|View full text |Cite
|
Sign up to set email alerts
|

Meta Analisis Pengaruh Problem Based Learning dan Virtual Laboratory Terhadap Hasil Belajar Siswa

Abstract: A meta-analysis was conducted to synthesize existing studies comparing the effects of Problem Based Learning and virtual laboratory versus traditional instructional media on student learning outcomes. Sixty-three studies were placed in this meta-analysis, and the results showed that Problem Based Learning and virtual laboratory learning media were more effective than instructional methods. The results of this study indicate that Problem Based Learning and virtual laboratory learning media clearly have a more p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 26 publications
0
5
0
4
Order By: Relevance
“…In their study, Kadir et al (2013) showed a similar result that the effect size of PBL implementation in enhancing students' problem-solving abilities in mathematics and science learning was 1,079, which is classified as a high effect size of the sixteen primary studies analyzed. Other empirical evidence (Puyada & Putra, 2018) in their meta-analysis study on twenty primary studies showed that PBL implementation positively affected student learning outcomes. Likewise, (Gijbels et al, 2005), in their meta-analysis study, showed that PBL implementation was significantly effective in increasing knowledge and skills of the 25 primary studies analyzed.…”
Section: Intervention Effects a The Overall Effect Size Of Each Studymentioning
confidence: 99%
See 2 more Smart Citations
“…In their study, Kadir et al (2013) showed a similar result that the effect size of PBL implementation in enhancing students' problem-solving abilities in mathematics and science learning was 1,079, which is classified as a high effect size of the sixteen primary studies analyzed. Other empirical evidence (Puyada & Putra, 2018) in their meta-analysis study on twenty primary studies showed that PBL implementation positively affected student learning outcomes. Likewise, (Gijbels et al, 2005), in their meta-analysis study, showed that PBL implementation was significantly effective in increasing knowledge and skills of the 25 primary studies analyzed.…”
Section: Intervention Effects a The Overall Effect Size Of Each Studymentioning
confidence: 99%
“…Analysis of publication bias and sensitivity is critical in ensuring statistical data validity in the meta-analysis process (Furuya-Kanamori & Doi, 2020;Tamur, Juandi, & Kusumah, 2020;Tamur, Mandur, & Pareira, 2021;Juandi et al, 2021). However, several meta-analysis studies do not apply publication bias and sensitivity (Batdi, 2014b(Batdi, , 2014aDochy et al, 2003;Gijbels et al, 2005;Kadir et al, 2013;Puyada & Putra, 2018). As a result, the resulting combined effect size tends to be over-interpreted and does not reflect the true effect (Tamur, Jehadus, Nendi, Mandur, & Murni, 2020).…”
Section: A Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meta-analisis sebelumnya, bagaimanapun, melaporkan tidak ada perbedaan yang signifikan pada hasil untuk siswa antara dua mode instruksi (Rahman, 2018). Meta-analisis yang lebih baru menemukan efek moderat untuk prestasi siswa dan kepuasan siswa dalam mendukung pembelajaran online (Puyada & Putra, 2018). Sebuah metaanalisis yang dilakukan oleh USDOE menemukan bahwa "siswa yang mengambil semua atau sebagian dari kelas mereka secara online tampil lebih baik, rata-rata, daripada mereka yang mengambil kursus yang sama melalui instruksi tatap muka tradisional" (Barokati & Annas, 2013); namun, lebih lanjut dalam penyelidikan studi yang digunakan dalam meta-analisis melaporkan kekurangan dalam metodologi (Unger leider & Burns, 2003).…”
Section: Pembelajaran Onlineunclassified
“…Namun, studi yang dilakukan pada strategi pembelajaran terkini yang digunakan untuk mengintegrasikan teknologi ke dalam kelas K-12 menunjukkan hasil yang beragam. Misalnya, meta-analisis yang dilakukan pada efek pembelajaran online menemukan efek moderat untuk prestasi siswa dan kepuasan siswa dalam mendukung pembelajaran online (Puyada & Putra, 2018). USDOE menemukan bahwa "siswa yang mengambil semua atau sebagian dari kelas mereka secara online berkinerja lebih baik, rata-rata, daripada mereka yang mengambil kursus yang sama melalui instruksi tatap muka tradisional" (Barokati & Annas, 2013).…”
Section: Kesimpulanunclassified